Stamps In The News: Geothermal Heat in Iceland - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2004)
A series of five stamps along with an informative booklet was recently issued (March 11, 2004) by the Iceland Post Office. The following are excerpts from this booklet